City design and its relationship with tourism crimes: a behaviour analysis of the urban environment. (1st January 2011) - Jackson, Mervyn; Inbakaran, Robert; Arrowsmith, Colin; George, Babu
This study explores city level design and its relationship to crime. We perform a comparative analysis between three tourist towns and three non-tourist control towns. The results found that tourist towns had a higher percentage of arterial roads to all roads (good prospect, quick escape) and that the percentage of streets with public space was four times as high (good prospect, good refuge, good escape). The implication for this is that tourist environments were designed for ready access of strangers and an increased tolerance of strangers in the community by hosts: both predictors of criminal behaviour. Future research should focus on designing out tourist crime victimisation by applying crime prevention through environmental design (CPTED).